Exploring the Influence of teacher student interaction strength, interaction time, interaction distance and interaction content on international student satisfaction with online courses - Wang, Xiaozhuan; Hassan, Aminuddin; Pyng, How Shwu; Ye, Han (Society for Research and Knowledge Management, 2022)
Since the outbreak of COVID-19 in January 2020, international online courses in universities in China have begun to develop on a large scale. This study explores the related influencing factors of teacher-student interaction on international student satisfaction with online courses in Chinese universities. It reveals which aspects of teacher-student interaction in online classes positively correlate with international students' satisfaction. This study is of a quantitative nature with four (independent variables (IVs) and one dependent variable (DV). The four IVs are the four dimensions of teacher-student interaction, namely interaction strength (IS), interaction time (IT), interaction content (IC), and interaction distance (ID). The DV is international student satisfaction (ISS) with online courses. This study was conducted in a university in Zhejiang Province, China. To answer the questionnaire, one hundred international students who were unable to enter China during COVID-19 were selected by stratified random sampling. The study used SPSS 21 to conduct descriptive and multiple linear regression analysis on the collected quantitative data. A total of 93 valid questionnaire data was collected. The analysis results showed that both IVs (IC & ID) have a positive correlation with the DV (ISS). Therefore, under the condition of limited equal resources, online teachers may give priority to the teacher-student interaction factors that have the greatest impact on the satisfaction of international students, carefully design teacher-student interaction activities, and maximise the satisfaction of international students.